Approximation of conjugate function related to Lipschitz and weighted class by product summability - Amarnath Kumar Thakur, Gopal Krishna Singh, Anjali Dubey (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The degree of approximation of the functions in Lipschitz spaces using single and product summability means has been studied by the authors. But so far nothing seems to happen in the direction of the present work. So, we established a theorem on degree of approximation of the conjugate function corresponding to the Lip and weighted class through the product sum of the conjugated Fourier series.